Laser additive repairing method for surface damage of undercarriage connecting lug
Through laser additive repair technology, powder and mobile laser cladding equipment with high contents of Cr and N are used for repairs one by one, and combined with laser impact enhancement and cold treatment, the problems of long repair cycle of landing gear ears and reduced plasticity of the material in the prior art are solved, achieving high efficiency and repair effects with performance close to the original.
Patent Information
- Application Number
- CN202411903587.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art provides a long repair cycle and leads to a reduced plastic properties of the material when repairing landing gear ear surface damage.
The laser additive repair method is used to prepare high-content Cr and N powders through vacuum induction melting inert gas atomization process, and repair them one by one using a mobile laser cladding equipment, and laser impact strengthening is carried out, and the repair effect is ensured through cold treatment and magnetic powder flaw detection.
It significantly shortens the repair cycle, improves the corrosion resistance and hardness of the repair area, and ensures that the repaired material performance is close to the original and has no cracks.
Smart Images

Figure CN119703114A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of remanufacturing technology, and in particular to a laser additive repair method for landing gear lug surface damage. Background Art
[0002] Aviation equipment in service in marine environments face severe corrosion tests. The landing gear lug is a key part that connects the fuselage to the landing gear. The landing gear lug part is in surface contact with the landing gear part, which is prone to surface cracks caused by the combined action of crevice corrosion and stress corrosion, causing damage to the integrity of the fuselage and threatening the service safety of aviation equipment.
[0003] Conventional wire feeding welding repair methods have the problems of low efficiency and long repair cycle. For example, patent CN115026460A discloses a method for preparing welding wire and a method for online repairing surface cracks of 1Cr15Ni4Mo3N substrate using the welding wire, which can be used for repairing the surface damage of landing gear lugs, including using micro-arc deposition cladding process for homogeneous material cladding, and then performing multi-layer alternating cladding on the welding wire. The repair cycle is long, and no relevant regulations are made on the plastic properties of the repaired material. Summary of the invention
[0004] In order to solve the problems of long conventional micro-arc deposition and welding repair cycle and the resulting reduction in plasticity, the present invention proposes a laser additive repair method for landing gear lug surface damage.
[0005] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0006] A method for laser additive repair of landing gear lug surface damage comprises the following steps:
[0007] S1. Use magnetic particle or dye flaw detection on the damaged landing gear ear parts to determine the damaged area, use an electric grinder to grind the damaged area to form a grinding area, and use a thickness gauge to measure the thickness of the grinding area. Grind 0.6-0.8mm, use magnetic particle or dye flaw detection to detect whether there is damage. If there is, grind again for 0.6-0.8mm, and use magnetic particle or dye flaw detection again until no microcracks or other damage are detected by magnetic particle or dye flaw detection. After grinding, the angle between the lower inclined surface of the grinding area and the vertical surface is 50°~70°, and the angle between the upper inclined surface of the grinding area and the vertical surface is 10°~20°. Use acetone to clean the grinding area.
[0008] S2. Using vacuum induction melting inert gas atomization process, using 1Cr15Ni4Mo3N high-strength steel rod and chromium iron nitride FeNCr10-A block as raw materials, using nitrogen for atomization, to prepare powder for laser additive repair, the element content of the prepared powder is as follows by mass percentage: C: 0.11% to 0.16%, Mn: 0.5% to 1.0%, Si≤0.7%, S≤0.02%, P≤0.03%, Cr: 15.5% to 16.5%, Ni: 4% to 5%, Mo: 2.3% to 2.8%, N: 0.1% to 0.2%, O≤0.04%, H≤0.005%;
[0009] Compared with conventional 1Cr15Ni4Mo3N material, the N content in the prepared powder is 0.1% to 0.2%, which is higher than the N content of 0.05% to 0.1% in the 1Cr15Ni4Mo3N material. The Cr content in the prepared powder is 15.5% to 17%, which is higher than the N content of 14.5% to 15.5% in the 1Cr15Ni4Mo3N material. The increase in the Cr content in the prepared powder will improve the corrosion resistance of the repaired area, while the increase in the N content will improve the hardness of the repaired area.
[0010] S3, using the powder prepared in step S2, using a mobile laser cladding equipment to perform cladding repair on the polished area, the light head in the mobile laser cladding equipment always keeps a horizontal direction, the angle between the light head and the end face of the powder head is 0.5° to 2.5°, the powder focus is located above the center line of the laser light path, the repair path is horizontal repair, the first repair path is located at the bottom of the polished area, and the repair is performed upwards one by one, each path is displaced upward by 0.8mm to 1.5mm, until a repair layer covering the entire polished area is formed;
[0011] S4. Perform laser shock peening on the repaired area of the part, polish the laser shock peening area with sandpaper of 1000 mesh or above, and then clean the damaged area with acetone;
[0012] S5, testing whether the repaired repaired area is higher than the surface of the ear part by more than 0.1 mm. If not, repeating steps S3 to S5 to form the next repair layer. If higher than 0.1 mm, stopping the laser additive repair.
[0013] S6. Prepare a cooling solution with a temperature of -116°C using ethanol and liquid nitrogen, and immerse the ear parts in the cooling solution for 1.5 to 2.5 hours;
[0014] S7. Polish and fine-tune the repaired landing gear lug parts to make the part size meet the use requirements;
[0015] S8, performing magnetic particle or color flaw detection on the polished landing gear lug parts to ensure that there are no cracks after repair. If cracks are found, repeat steps S3 to S7 to carry out repairs, and perform magnetic particle or color flaw detection again until no cracks are found after magnetic particle or color flaw detection.
[0016] S9. Prepare test pieces to verify the repair effect:
[0017] The test piece is made of the corresponding grade material under the same heat treatment state as the landing gear lug part, and is made into a repaired part and a reference part. The repaired part is a test piece with artificial defects and repaired, and the reference part is a test piece treated by the heat treatment process during the manufacturing of the landing gear lug. The performance of the repaired part and the reference part are compared to judge the effect after the repair. The surface of the repaired part is artificially processed to a depth equivalent to the thickness of the defect removed in step S1, and the powder prepared in step S2 is used for laser additive repair. The repaired part is the laser additive repair area. The repair process repeats steps S3 to S6. The repaired part and the reference part are processed into tensile test specimens and fatigue test specimens. Observe the fracture position of the tensile test specimen, compare the tensile strength of the repaired part with that of the reference part, the elongation after fracture of the repaired part with that of the reference part, and the fatigue performance of the repaired part with that of the reference part. The fatigue test load is 800MPa and the stress ratio is 0.1. If it does not break after 15,000 times, it is considered to have passed. If the average tensile strength of the repaired part reaches more than 99% of the performance of the reference part, and the average elongation after fracture of the repaired part reaches more than 95% of the performance of the reference part, the fracture position of the tensile test specimen of the repaired part is located in the matrix rather than the laser additive repair area, and the fatigue performance of the repaired part passes the fatigue test, it is determined that the landing gear ear part has been repaired successfully.
[0018] As a further improvement of the present invention, the specific process of the vacuum induction melting inert gas atomization process in step S2 is as follows:
[0019] The first step: put the 1Cr15Ni4Mo3N rod into the crucible in the smelting chamber for smelting, and put the chromium iron nitride FeNCr10-A block into the charging bin;
[0020] Step 2: The melting chamber is evacuated. When the pressure drops below 10Pa, argon is filled in until the pressure in the melting chamber reaches atmospheric pressure, and then the chamber is evacuated to 10Pa. This process is repeated three times.
[0021] Step 3: Fill with argon gas to 0.1MPa, start power smelting, heat the temperature to 1650℃, melt the master alloy completely, pour the chromium iron nitride FeNCr10-A block in the charging bin into the crucible, make it fully dissolved in the high-temperature melt, pour the molten metal in the crucible into the tundish, the molten metal flows out from the leakage pipe under the tundish, use high-purity nitrogen to impact the molten metal liquid flow to form small droplets, the metal droplets are cooled in the cooling chamber and collected in the powder collecting tank;
[0022] Step 4: Use 100-mesh and 270-mesh sieves to sieve out the powder, and select 53μm to 150μm powder as repair powder.
[0023] As a further improvement of the present invention, the mass ratio of chromium ferronitride FeNCr10-A block to 1Cr15Ni4Mo3N rod in the vacuum induction melting inert gas atomization process is 2.5% to 5%, the nitrogen pressure is 2.2MPa-3.2MPa, and the leakage diameter of the leakage tube is 4mm-7mm.
[0024] As a further improvement of the present invention, the repair parameters of the mobile laser cladding equipment in step S3 are: laser power of 700W to 1200W, spot diameter of 1mm to 1.4mm, cladding head moving rate of 8mm / s to 14mm / s, powder feeding gas argon flow rate of 2L / min to 5L / min, protective gas argon flow rate of 9L / min to 12L / min, powder feeding disk speed of 0.4rpm-0.9rpm, vertical distance between cladding head and repair area of 8mm to 10mm, control the initial temperature of laser cladding repair process not higher than 35°C, and the end temperature of single-pass cladding not higher than 70°C.
[0025] As a further improvement of the present invention, the laser shock peening process parameters in step S4 are: laser energy is 4J-6J, spot size is 2mm-3mm, and overlap rate is 40%-60%.
[0026] As a further improvement of the present invention, before each repetition of the laser additive repair process in step S5, the laser cladding head consisting of the light output head and the powder output head is moved away from the repair area of the landing gear ear part by 0.5 mm to 0.8 mm, until the repair area of the landing gear ear part is higher than the surface of the landing gear ear part by more than 0.1 mm.
[0027] As a further improvement of the present invention, the preparation process in step S6 is: slowly adding liquid nitrogen to the ethanol solution until a portion of the ethanol solution solidifies.
[0028] The beneficial effects of the present invention are:
[0029] The present invention provides a method for laser additive repair of landing gear lug surface damage, which, compared with the prior art:
[0030] 1. By designing the angle between the lower slope of the grinding area and the vertical surface to be 50°~70°, the powder can be easily deposited on the slope during the laser cladding process, thereby improving the repair efficiency. The angle between the upper slope of the grinding area and the vertical surface is 10°~20°, which increases the powder escape space and is less likely to form unfused defects caused by narrow space;
[0031] 2. By using 1Cr15Ni4Mo3N high-strength steel bars and chromium iron nitride FeNCr10-A blocks to prepare powder, the Cr and N contents of the prepared powder are higher than those of 1Cr15Ni4Mo3N material. The increase in Cr content in the powder will improve the corrosion resistance of the repaired area, while the increase in N content will improve the hardness of the repaired area, thereby achieving a better effect;
[0032] 3. Nitrogen is used instead of conventional argon for atomization, which reduces the cost of preparing powder and further supplements the N content in the powder material. The nitrogen pressure is 2.2MPa-3.2MPa, which is relatively low, which is conducive to the formation of high sphericity powder, the number of hollow powder in the powder is reduced, and the required 53μm-150μm particle size range of powder is increased;
[0033] 4. Adjust the angle between the end face of the light outlet head and the powder outlet head to 0.5°~2.5° by adjusting the screw, so that the powder focus deviates from the center line of the laser light path, and the powder focus is located above the center line of the laser light path, thereby offsetting part of the gravity effect, increasing the amount of powder that can be clad on the melt path, and improving the cladding efficiency;
[0034] 5. Cold treatment using a -116°C cooling bath solution made of ethanol and liquid nitrogen will promote the complete transformation of austenite to martensite. Since the N content in the prepared powder is higher than that of 1Cr15Ni4Mo3N material, its austenite stability will also be higher. It is necessary to promote the transformation of austenite to martensite in the cladding layer at a lower temperature to increase the strength of the cladding layer area.
[0035] 6. Through step-by-step laser shock strengthening treatment, the residual tensile stress in the cladding layer area is eliminated, and the fatigue performance of the repaired tissue is improved;
[0036] 7. The repair effect is verified by preparing test pieces, avoiding destructive testing of parts, and also verifying the performance after repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The present invention is further described below in conjunction with the accompanying drawings and embodiments:
[0038] Figure 1 It is a schematic diagram of the structure of the landing gear lug parts;
[0039] Figure 2 This is the cross-sectional view of the damaged part of the landing gear lug after polishing;
[0040] Figure 3 is a cross-sectional view of the laser cladding head;
[0041] Figure 4 This is a schematic diagram of laser additive repair step by step;
[0042] Figure 5This is a picture of the tensile specimen of the repaired part after the tensile test.
[0043] In the figure: 1. Landing gear ear parts; 2. Grinding area; 3. Polishing head; 4. Powder head; 5. Powder focus; 6. Center line of laser light path; 7. Melt channel; 8. Laser additive repair area; 9. Fracture location. DETAILED DESCRIPTION
[0044] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below with reference to the accompanying drawings and embodiments.
[0045] A method for laser additive repair of landing gear lug surface damage comprises the following steps:
[0046] S1, such as Figure 1 As shown in FIG. 1 , a landing gear lug part 1 is used for a damaged landing gear lug part 1. A magnetic particle inspection is performed on the damaged landing gear lug part 1 to determine the damaged area. An electric grinder is used to grind the damaged area to form a grinding area 2. Figure 2 As shown; grind 0.8mm each time, use magnetic particle inspection to detect whether there is any damage. If there is, grind again by 0.6mm until multiple grindings are performed until no damage such as microcracks is detected by magnetic particle inspection. After grinding, the angle between the lower inclined surface of the grinding area 2 and the vertical surface is 60°, and the angle between the upper inclined surface of the grinding area 2 and the vertical surface is 15°. Use acetone to clean the grinding area 2.
[0047] S2. Use vacuum induction melting and inert gas atomization process to prepare powder for laser additive repair.
[0048] Use 1Cr15Ni4Mo3N high-strength steel bars and chromium nitride FeNCr10-A blocks as raw materials, put the 1Cr15Ni4Mo3N bars into the crucible in the smelting chamber for smelting, put the chromium nitride FeNCr10-A blocks into the charging bin, evacuate the smelting chamber, and when the pressure drops below 10Pa, fill with argon until the pressure in the smelting chamber reaches atmospheric pressure, then evacuate to 10Pa, repeat three times, fill with argon to 0.1MPa, start power smelting, and heat to the temperature. 1650℃, melt the master alloy completely, pour the chromium ferronitride FeNCr10-A block in the charging bin into the crucible, and after it is fully dissolved in the high-temperature melt, pour the molten metal in the crucible into the tundish, and the molten metal flows out from the leakage pipe under the tundish. Use high-purity nitrogen to impact the molten metal flow to form small droplets. The metal droplets are cooled in the cooling chamber and collected in the powder collecting tank. Use 100 mesh and 270 mesh sieves to screen the powder, and screen out 53μm~150μm powder as repair powder.
[0049] The mass of the 1Cr15Ni4Mo3N rod used in the above process is 20kg, the mass of the ferrochromium nitride FeNCr10-A block used is 0.5kg, the mass ratio of the ferrochromium nitride FeNCr10-A block to the 1Cr15Ni4Mo3N rod is 2.5%, the nitrogen pressure is 2.5MPa, and the leakage diameter of the leakage pipe is 6mm.
[0050] The element contents of the prepared powder are as follows by mass percentage: C: 0.13%, Mn: 0.59%, Si: 0.5%, S: 0.003%, P: 0.003%, Cr: 15.8%, Ni: 4.5%, Mo: 2.4%, N: 0.14%, O: 0.022%, and H: 0.002%. Compared with conventional 1Cr15Ni4Mo3N material, the N content in the prepared powder is 0.14%, which is higher than the N content of 0.05% to 0.1% in the 1Cr15Ni4Mo3N material, and the Cr content in the prepared powder is 15.8%, which is higher than the N content of 14.5% to 15.5% in the 1Cr15Ni4Mo3N material.
[0051] The increase of Cr content in the prepared powder will improve the corrosion resistance of the repaired area, while the increase of N content will improve the hardness of the repaired area.
[0052] S3, using the powder prepared in step S2, using a mobile laser cladding device to perform cladding repair on the polished area 2, the light head 3 in the mobile laser cladding device always keeps a horizontal direction, the angle between the light head 3 and the end face of the powder head 4 is 1°, and the powder focus 5 is located above the center line 6 of the laser light path, such as Figure 3 The repair path is horizontal repair, the first repair path 7 is located at the bottom of the grinding area 2, and the repair is performed upwards, each path is displaced upwards by 0.8mm to 1.5mm, until a repair layer covering the entire grinding area 2 is formed, as shown in FIG. Figure 4 shown.
[0053] The repair parameters of the mobile laser cladding equipment are as follows: laser power is 800W, spot diameter is 1.1mm, cladding head moving rate is 10mm / s, powder feeding gas argon flow rate is 4L / min, shielding gas argon flow rate is 10L / min, powder feeding disk speed is 0.6rpm, and the vertical distance between the cladding head and the repair area is 10mm.
[0054] S4. Perform laser shock peening on the repaired area of the part. The laser shock peening process parameters are: laser energy 4J, spot size 2.5mm, overlap rate 50%. Use 1000 mesh or above sandpaper to polish the laser shock peening area, and then use acetone to clean the damaged area.
[0055] S5. Test whether the repaired repaired area is higher than the surface of the ear part by more than 0.1mm. In this embodiment, if it is not higher than 0.1mm, repeat steps S3 to S5 to form the next repair layer. Before each laser additive repair process, the laser cladding head composed of the light head 3 and the powder head 4 is moved away from the repair area by 0.6mm. The laser additive repair process is repeated twice. At this time, the total repair layer height is 1.8mm, and the height of the polished area is 1.4mm. The repair area of the ear part is 0.4mm higher than the surface of the ear part, and the laser additive repair is stopped.
[0056] S6. Use ethanol and liquid nitrogen to prepare a cooling solution with a temperature of -116°C. The preparation process is: slowly add ethanol to the ethanol solution until part of the ethanol solution solidifies. Soak the ear parts in the cooling solution for 2 hours.
[0057] S7. Grind and fine-tune the repaired landing gear lug part 1 so that the part size meets the use requirements.
[0058] S8. Perform magnetic particle inspection on the polished landing gear ear part 1 to ensure that there are no cracks after repair. No cracks were found.
[0059] S9. Prepare test pieces to verify the repair effect:
[0060] The material of the test piece is the corresponding grade material of the landing gear ear parts, the grade is 1Cr15Ni4Mo3N material.
[0061] The test piece was treated with the heat treatment process used during the manufacturing of the landing gear lug, specifically 1050℃×60min, oil cooling; -70℃×2h, air cooling; 350℃×3h, air cooling.
[0062] The test pieces include repaired pieces and reference pieces. The repaired pieces are test pieces with artificial defects and repairs, while the reference pieces are heat treated using the same process used when manufacturing landing gear lugs. The performance of the repaired pieces and reference pieces is compared to judge the repair results.
[0063] The repaired part surface is artificially processed to a depth equivalent to the defect removed in step S1, and the powder prepared in step S2 is used for laser additive repair. The repaired part is the laser additive repair area 8. The repair process repeats steps S3 to S6. The repaired part and the reference part are processed into tensile test specimens and fatigue test specimens. The fracture position 9 of the tensile test specimen is visually observed. The tensile strength of the repaired part is compared with the tensile strength of the reference part, the elongation after fracture of the repaired part is compared with the elongation after fracture of the reference part, and the fatigue performance of the repaired part is compared with the fatigue performance of the reference part. The fatigue test load is 800MPa and the stress ratio is 0.1. If it is not broken after 15,000 times, it is considered to be passed. If the average tensile strength of the repaired part reaches more than 99% of the performance of the reference part, the average elongation after fracture of the repaired part reaches more than 95% of the performance of the reference part, the fracture position 9 of the tensile test specimen of the repaired part is located in the substrate rather than the laser additive repair area 8, and the fatigue performance of the repaired part passes the fatigue test, it is determined that the landing gear lug part has been repaired successfully.
[0064] In this embodiment, a 1mm-deep defect is artificially processed on the surface of the repaired part, and the repair process follows the ear-jointed part repair process. The tensile strength of the reference part was measured to be 1440MPa, 1450MPa, and 1451MPa. The tensile strength of the repaired part was measured to be 1438MPa, 1444MPa, and 1448Mpa. The average tensile strength of the reference part was 1447MPa, and the average tensile strength of the repaired part was 1443MPa, and the tensile strength of the repaired part reached 99.7% of the reference part. The tensile strength of the reference part was measured to be 1440MPa, 1450MPa, and 1451MPa. The tensile strength of the repaired part was measured to be 1439MPa, 1444MPa, and 1448Mpa. The average tensile strength of the reference part was 1447MPa, and the average tensile strength of the repaired part was 1443.6MPa, and the tensile strength of the repaired part reached 99.7% of the reference part. The measured elongation after fracture of the repaired parts was 16.5%, 18%, and 18.5%. The measured elongation after fracture of the reference parts was 18%, 16.5%, and 18%. The average elongation after fracture of the repaired parts was 17.66%, and the average elongation after fracture of the repaired parts was 17.5%. The elongation after fracture of the repaired parts reached 99% of that of the reference parts. Visual observation revealed that the fracture positions of the tensile test specimens of the repaired parts 9 were all located in the matrix rather than the laser additive repair area 8, as shown in the figure. Figure 5 shown.
[0065] The fatigue test load is 800MPa, the stress ratio is 0.1, and it is considered passed if it does not break after 15,000 times. The three reference parts and three repaired parts did not break after 15,000 fatigue tests. The tensile strength of the repaired parts reached more than 99% of the performance of the reference parts, and the elongation after fracture reached more than 95% of the performance of the reference parts. The fatigue performance passed the fatigue test, and it was determined that the landing gear ear part 1 was successfully repaired.
[0066] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A laser additive repair method for landing gear lug surface damage, characterized in that: The following steps are involved: S1. Use magnetic powder or dye flaw detection on the damaged landing gear ear part (1) to determine the damaged area, use an electric grinder to grind the damaged area to form a grinding area (2), grind 0.6-0.8 mm, use magnetic powder or dye flaw detection to detect whether there is damage, if there is, grind again 0.6-0.8 mm until no microcrack damage is detected by magnetic powder or dye flaw detection, the angle between the lower inclined surface of the grinding area (2) and the vertical surface after grinding is 50°-70°, and the angle between the upper inclined surface of the grinding area (2) and the vertical surface is 10°-20°, and the grinding area (2) is cleaned with acetone; S2. Using vacuum induction melting inert gas atomization process, using 1Cr15Ni4Mo3N high-strength steel rod and chromium iron nitride FeNCr10-A block as raw materials, using nitrogen for atomization, to prepare powder for laser additive repair, the element content of the prepared powder is as follows by mass percentage: C: 0.11% to 0.16%, Mn: 0.5% to 1.0%, Si≤0.7%, S≤0.02%, P≤0.03%, Cr: 15.5% to 16.5%, Ni: 4% to 5%, Mo: 2.3% to 2.8%, N: 0.1% to 0.2%, O≤0.04%, H≤0.005%; S3, using the powder prepared in step S2, using a mobile laser cladding device to perform cladding repair on the grinding area (2), the light head (3) in the mobile laser cladding device always maintains a horizontal direction, the angle between the light head (3) and the end face of the powder head (4) is 0.5° to 2.5°, the powder focus (5) is located above the center line (6) of the laser light path, the repair path is horizontal repair, the melt path (7) formed by the first repair is located at the bottom of the grinding area (2), and the repair is performed upwards one by one, with each path moving upwards by 0.8 mm to 1.5 mm, until a repair layer covering the entire grinding area (2) is formed; S4. Perform laser shock peening on the repaired area of the part, polish the laser shock peening area with sandpaper of 1000 mesh or above, and then clean the damaged area with acetone; S5, testing whether the repaired repaired area is higher than the surface of the ear part by more than 0.1 mm. If not, repeating steps S3 to S5 to form the next repair layer. If higher than 0.1 mm, stopping the laser additive repair. S6. Prepare a cooling solution with a temperature of -116°C using ethanol and liquid nitrogen, and immerse the ear parts in the cooling solution for 1.5 to 2.5 hours; S7, polishing and finishing the repaired landing gear lug part (1) to make the part size meet the use requirements; S8, performing magnetic particle or color flaw detection on the polished landing gear lug part (1) to ensure that there are no cracks after the repair. If cracks are found, steps S3 to S7 can be repeated to carry out the repair, and magnetic particle or color flaw detection can be carried out again until no cracks are found after the magnetic particle or color flaw detection. S9. Prepare test pieces to verify the repair effect: The test piece is made of the same grade of material as the landing gear lug part (1) under the same heat treatment state, and is made into a repaired part and a reference part. The repaired part is a test piece with artificial defects and repaired, and the reference part is a test piece treated by the heat treatment process during the manufacturing of the landing gear lug. The tensile strength, elongation after fracture and fatigue performance of the repaired part and the reference part are compared. If the fatigue test load is 800MPa, the stress ratio is 0.1, and it does not break after 15,000 times, it is considered to have passed. If the average tensile strength of the repaired part reaches more than 99% of the performance of the reference part, the average elongation after fracture of the repaired part reaches more than 95% of the performance of the reference part, and the fracture position (9) of the repaired part is not located on the laser additive repair area (8), then it is determined that the landing gear lug part has been repaired successfully.
2. The method for laser additive repair of landing gear lug surface damage according to claim 1, characterized in that: The specific process of the vacuum induction melting inert gas atomization process in step S2 is as follows: The first step: put the 1Cr15Ni4Mo3N rod into the crucible in the smelting chamber for smelting, and put the chromium iron nitride FeNCr10-A block into the charging bin; Step 2: The melting chamber is evacuated. When the pressure drops below 10Pa, argon is filled in until the pressure in the melting chamber reaches atmospheric pressure, and then the chamber is evacuated to 10Pa. This process is repeated three times. Step 3: Fill with argon gas to 0.1MPa, start power smelting, heat the temperature to 1650℃, melt the master alloy completely, pour the chromium iron nitride FeNCr10-A block in the charging bin into the crucible, make it fully dissolved in the high-temperature melt, pour the molten metal in the crucible into the tundish, the molten metal flows out from the leakage pipe under the tundish, use high-purity nitrogen to impact the molten metal liquid flow to form small droplets, the metal droplets are cooled in the cooling chamber and collected in the powder collecting tank; Step 4: Use 100-mesh and 270-mesh sieves to sieve out the powder, and select 53μm to 150μm powder as repair powder.
3. The method for laser additive repair of landing gear lug surface damage according to claim 2, characterized in that: In the vacuum induction melting inert gas atomization process, the mass ratio of chromium ferronitride FeNCr10-A block to 1Cr15Ni4Mo3N rod is 2.5% to 5%, the nitrogen pressure is 2.2MPa-3.2MPa, and the leakage hole diameter of the leakage tube is 4mm-7mm.
4. The method for laser additive repair of landing gear lug surface damage according to claim 1, characterized in that: The repair parameters of the mobile laser cladding equipment in step S3 are as follows: laser power is 700W-1200W, spot diameter is 1mm-1.4mm, cladding head moving speed is 8mm / s-14mm / s, powder feeding gas argon flow rate is 2L / min-5L / min, shielding gas argon flow rate is 9L / min-12L / min, powder feeding disk speed is 0.4rpm-0.9rpm, the vertical distance between the cladding head and the repair area is 8mm-10mm, the initial temperature of the laser cladding repair process is controlled not to be higher than 35°C, and the end temperature of a single cladding pass is not higher than 70°C.
5. The method for laser additive repair of landing gear lug surface damage according to claim 1, characterized in that: The laser shock peening process parameters in step S4 are: laser energy of 4J-6J, spot size of 2mm-3mm, and overlap rate of 40%-60%.
6. The method for laser additive repair of landing gear lug surface damage according to claim 1, characterized in that: Before each repetition of the laser additive repair process in step S5, the laser cladding head composed of the light discharge head (3) and the powder discharge head (4) is moved away from the repair area of the landing gear lug part (1) by 0.5 mm to 0.8 mm until the repair area of the landing gear lug part (1) is higher than the surface of the landing gear lug part (1) by more than 0.1 mm.
7. The method for laser additive repair of landing gear lug surface damage according to claim 1, characterized in that: The preparation process in step S6 is: slowly adding liquid nitrogen to the ethanol solution until part of the ethanol solution solidifies.
Citation Information
Cited By
Clutch retainer precise additive repair method based on laser cladding technology
CN120325993A